Daniel A. Carrion as a researcher: A methodological analysis of the Carrion experience - Alarcón Villaverde, José (1998)
A methodological analysis of Carrion experiment, based upon his most important papers published after his death, such as «Notes regarding Peruvian wart» as well as a clinical case self-record of the natural history of his illness since his auto-inoculation until his death in 1885, was made. The contemporary predominant ideas of those years, together with the most recent foreign acknowledgments toward Carrion contribution to both epidemiological and medical sciences, were pointed out. We concluded that Carrion was an original researcher at due to the way he approached the problem of the Peruvian warm disease. He was also very original researcher at hypothesizing an explanation that he finally would try on himself. Besides he emerged as an acute observer as well as an accurate researcher and a great classical scholar.